Representation Of Moral Messages In The Short Film 'Self' (2024) By Raihan Ananda Pratama: A Peircean Semiotics Analysis - Eko Hadi Prayitno; Juju Masunah; Zakarias S. Soeteja; Hery Supiarza (INJECT (Interdisciplinary Journal of Communication), 2025)
This article is a description of the results of a semiotic study of a short film entitled "Self" in the representation of moral messages. The research approach uses the theory of communication semiotics to reveal the meaning of each form of representation of moral messages. Data collection is carried out through observation and semi-structured interviews. Data analysis uses the theory of the semiotic triangle by Charles Sanders Peirce. This study shows that in each plot of the film, it tries to convey that bullying has a bad impact on its victims. The moral messages in the film have been represented in an audio visual such as images and narration that can be understood by participants. This study attempts to provide an overview that the film "Self" has a moral message. Thus, this research can provide an overview that short films can briefly convey moral messages as an information medium.